Analisis Kajian Struktural Dan Nilai Kearifan Lokal Dalam Hikayat “Si Baroar” Etnis Mandailing - Evi Rizkita Dewi; Emasta Evayanti Simanjuntak (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The research aims to analyze structural studies and local wisdom values in the hikayat Si Baroar that developed in the Mandailng Natal community. The research uses descriptive analytical method, which is a method that describes as clearly as possible about the object under study, and describes the data thoroughly, systematically, and accurately. The analysis is carried out using the theoretical basis used, then analyzed and interpreted in accordance with the theoretical study so that the research results can later describe the problems studied objectively, systematically based on the theories that the author uses. Based on the results of this study, it can be concluded that Si Baroar is a saga originating from the Mandailing Natal area. There are instrinsic elements, namely: Theme, character, and plot. There are also local wisdom values in the Si Baroar saga